2012
DOI: 10.1242/jeb.064618
|View full text |Cite
|
Sign up to set email alerts
|

Do ants need to be old and experienced to teach?

Abstract: SUMMARYLearning is widespread in invertebrates. However, whether social insects improve their recruitment skills with experience is only beginning to be investigated. Tandem running is a one-to-one form of recruitment used by certain species of ant. It is a remarkable communication system that meets widely accepted criteria for teaching in non-human animals. Here, we determined experimentally to what extent participation in, and efficient execution of, tandem running depends on either the age or the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Most empirical studies on the effect of experience in social insects have focused on the first aspect, namely on experienced‐based changes in task performance, for example, in foraging (O'Donnell & Jeanne, ; Chittka & Thomson, ; Peat & Goulson, ; Raine & Chittka, ), undertaking (Visscher, ), orientation (Wolf & Wehner, ), nest moving (Langridge et al , ), brood care (Muscedere, Willey & Traniello, ; Weidenmüller et al , , but see Muscedere, Djermoun & Traniello, ) or recruitment (Franklin et al , ; but see Dornhaus, ).…”
Section: Proximate Causes ‐ How Do Interindividual Differences Arise?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most empirical studies on the effect of experience in social insects have focused on the first aspect, namely on experienced‐based changes in task performance, for example, in foraging (O'Donnell & Jeanne, ; Chittka & Thomson, ; Peat & Goulson, ; Raine & Chittka, ), undertaking (Visscher, ), orientation (Wolf & Wehner, ), nest moving (Langridge et al , ), brood care (Muscedere, Willey & Traniello, ; Weidenmüller et al , , but see Muscedere, Djermoun & Traniello, ) or recruitment (Franklin et al , ; but see Dornhaus, ).…”
Section: Proximate Causes ‐ How Do Interindividual Differences Arise?mentioning
confidence: 99%
“…the individual response probability, depending on previous experience (Ravary et al , ; Robinson et al , ). Experienced Temnothorax albipennis ants are more likely to engage in tandem runs and more likely to lead tandem runs (Franklin et al , ). Oster & Wilson () suggested that insects that do a job successfully are more likely to repeat that particular type of activity when the opportunity is next presented.…”
Section: Proximate Causes ‐ How Do Interindividual Differences Arise?mentioning
confidence: 99%
“…Groups of individuals repeatedly engage in collective task execution and modify their strategies based on the rewards they receive individually or collectively. This framework is aligned with empirical evidence identifying social interactions and ecology as key factors [18,49,50,36,25,28,11]. This modelling framework provides a large degree of flexibility via simulations, while also allowing for mathematical predictions based on game theory [31].…”
Section: Introductionmentioning
confidence: 99%
“…; Franklin et al. ) and social interaction pattern (Powell & Tschinkel ) may also influence the probability that it will perform a given task. Furthermore, a worker's spatial location may affect its rate of encounters with a stimulus and the level of stimulation experienced (Fresneau et al.…”
Section: Introductionmentioning
confidence: 99%